ANALISIS PEMECAHAN MASALAH MODEL POLYA UNTUK MENYELESAIKAN SOAL CERITA PADA PEMBELAJARAN MATEMATIKA KELAS IV - Dian Aprinda Putri; Mukti Sintawati; Siwi Aminah (PeTeKa (Jurnal Penelitian Tindakan Kelas dan Pengembangan Pembelajaran), 2022)
The purpose of this study was to determine the steps in solving math problem problems using the Polya model problem solving method for grade IV students. This research approach is qualitative with descriptive methods. The subjects of this study were students of class IV MI Al-Madina Prambanan in the academic year 2020/2021, with 8 students. The research sample was 3 students with high, medium, and low math abilities. The data collection technique used in this study was a test by giving 5 items of Mathematics story questions, and interviews with students and interviews with the fourth grade homeroom teacher as source triangulation. The data analysis technique used is data reduction, data presentation, verification. The results of this study indicate that students with high-level abilities are able to solve Mathematics problems using the Polya model in questions number 2 to 5 starting from understanding problems, planning problems, solving problems, and drawing conclusions with the right steps, there is one mistake made, namely in question number 1 does not write a conclusion. Students with moderate ability levels are able to complete the four steps of Polya coherently in questions number 1, 3, and 5. Questions number 2 and 4 do not write conclusions and experience errors at the problem solving stage. Students with low-level abilities in solving problems in questions 3 and 4 do not plan the problems to be faced, questions number 1, 2, and 4 do not provide solutions.